Identifying the optimal candidates for locoregional radiation therapy in patients with de novo metastatic nasopharyngeal carcinoma. Issue 9 (27th April 2021) - Xu, Hanchuan; Lu, Lihu; Lu, Tianzhu; Xu, Yun; Zong, Jingfeng; Huang, Chaobin; Lin, Fengjie; Zheng, Yahan; Lin, Cheng; Lin, Senan; Qiu, Sufang; Pan, Jianji; et al.
Abstract: Background: To evaluate the value of locoregional radiation therapy (LRRT) in de novo metastatic nasopharyngeal carcinoma (mNPC) and identify suitable candidates for additional LRRT after palliative chemotherapy (PCT). Methods: Patients with de novo mNPC received platinum‐based chemotherapy for a minimum of four cycles with or without definitive LRRT via intensity‐modulated radiation therapy (IMRT) were all candidates for this study. Results: A total of 168 patients were included for this analysis. Additional LRRT was associated with significantly longer median OS (69.5 vs. 17.8 months, p < 0.001) when compared with PCT alone. However, this survival benefit of LRRT was only reflected in patients with oligometastatic diseases (90.8 vs. 17 months, p < 0.001), but not for those with polymetastatic disease ( p = 0.86). Conclusions: Additional LRRT after PCT may only improve OS for oligometastatic patients. For patients with polymetastatic disease, intensive systemic treatment such as the combination of immunotherapy and adequate PCT might be necessary.